MENGURAI TANTANGAN MENOPAUSE PREKOKS: DAMPAKNYA TERHADAP KUALITAS HIDUP WANITA - Nardina, Evita Aurilia; Dewi, Ratih kumala; Astuti, Etni Dwi (Jurnal Ilmu Keperawatan dan Kebidanan, 2025)
Premature menopause, occurring before the age of 40, can significantly impact women’s quality of life, encompassing physical, psychological, social, and environmental aspects. This study aims to identify factors associated with the quality of life of women experiencing premature menopause at Krobokan Public Health Center. The research design is cross-sectional, involving 98 respondents selected through purposive sampling. Quality of life was measured using the Menopause Specific Quality of Life Questionnaire (MENQOL). Chi-square test results showed significant associations between age (p-value = 0.017), educational level (p-value = 0.040), and the use of hormonal contraception (p-value = 0.027) with quality of life. However, employment and health history variables did not show significant associations (p-values = 0.061 and 0.055, respectively). These findings highlight the importance of targeted reproductive health intervention programs and education to improve the quality of life for women experiencing premature menopause.